AN EXPERIMENTAL STUDY OF THE AERODYNAMICS FORCES ACTING ON A TRUCK - Mustofa, Mustofa (MEKTEK, 2009)
The aim of this project is to show the aerodynamics experiment results of a truck in terms of drag coefficient (Cd) within aerodynamics forces. The test was conducted in the Wind Tunnel laboratory at the University of South Australia in the school of Mechanical and Manufacturing Engineering. In addition to the test, fairing and without fairing effects were investigated. Results, Cd truck with fairing was lower than that of with fairing by 0.108 or from 1.518 to 1.41. By adding the fairing on the truck’s cap, fuel consumption could be saved